PENERAPAN BUERGER ALLEN EXERCISE MENGURANGI RISIKO GANGGUAN PERFUSI PERIFER PADA PASIEN DIABETES MELITUS DI WILAYAH PUSKESMAS SIDOREJO - Zuraidah S; Susmini; Bambang Soewito; Indah Dewi Ridawati; Triana Swampera (Institut Kesehatan Hermina, 2024)
ABSTRACT Diabetes Mellitus is a disease that has hyperglycemia caused by a decrease in the ability of the pancreas to secrete insulin. High blood sugar levels can disrupt platelet function and lead to the formation of blood clots and therefore, diabetic patients are at risk of developing peripheral arterial disease. The risk of ineffective peripheral perfusion can be overcome with non-pharmacological measures, namely the Buerger Allen Exercise (BAE). The Buerger Allen exercise is easy to do, such as doing muscle contractions by applying changes in the position of gravitational force and muscle pumps by applying foot and ankle movements to smooth blood vessels. This research uses a qualitative design type with a case study method. This research was carried out on subject I on 17-21 March and on subject II 23-27 March 2024 in the working area of ??the Sidorejo Health Center, Lubuklinggau City. The inclusion criteria in this study were patients aged 40 - 45 years who had no wounds, while the exclusion criteria were DM patients with other comorbidities such as asthma, fractures, gastritis who had gangrene and wounds. Data collection was carried out by observation and interviews using instruments in the form of ABI sheets, Buerger Allen Exercise SOP. In this study, the results obtained after carrying out the Buerger Allen Exercise were that both patients reported reduced complaints of tingling and itching, and blood glucose levels decreased. The Buerger Allen Exercise intervention has proven to be effective in